AN ANALYSIS OF TRANSLATION STRATEGY OF IDIOMATIC EXPRESSIONS IN “ONWARD” MOVIE SUBTITLE - Herlia Indriana; Indah Tri Purwanti; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: From the difficulty and necessity to mastering English as it is almost useful in every life aspect nowadays, the writer decides to conduct this study to examines the translation strategy of idiomatic expressions in Onward movie subtitles. It is a descriptive qualitative method one, aiming to find out the types of idiomatic expressions and the strategy employed to translate it. The two objectives are answered by applying Adelnia and Dastjerdi’s (2011) theory and Baker’s (2011) theory consecutively. The findings shows that colloquialism is the most frequent form of idiomatic expression that appears, with 150 (41,6%) total findings. Phrasal verbs come close in the second place with 145 (40,2%) total findings, Slang comes in third place with 64 (17,7%) total findings. Meanwhile, proverbs and allusions tied for last place, with only one finding for each of them. In total, the subtitle of Onward movie contains 361 idiomatic expressions. The second research question is about how the idiomatic expressions in Onward movie’s subtitles are translated. The results identify 212 (57,9%) occurrences of paraphrase as the strategy used to interpret the idiomatic expressions present in the movie, making it the most commonly used strategy. Contrary to this, the translator never uses borrowing from the source language or the omission of a play on idioms as their strategy to translate idiomatic expressions in the movie. The differences in culture of both languages may be the biggest factor of why the translator chooses to use paraphrasing to translate the idiomatic expressions in Onward movie subtitles.Key Words: Translation Strategy, Idioms, Movie.